Respuesta :

Answer:

[tex]x=-2\\x=2[/tex]

(You only need to give one solution)

Step-by-step explanation:

We have the following equation

[tex](x^2+1)^2-5x^2-5=0[/tex]

First, we need to foil out the parenthesis

[tex]x^4+2x^2+1-5x^2-5=0[/tex]

Now we can combine the like terms

[tex]x^4-3x^2-4=0[/tex]

Now, we need to factor this equation.

To factor this, we need to find a set of numbers that add together to get -3 and multiply to give us -4.

The pair of numbers that would do this would be 1 and -4.

This means that our factored form would be

[tex](x^2-4)(x^2+1)=0[/tex]

As the first binomial is a difference of squares, it can be factored futher into

[tex](x^2+1)(x+2)(x-2)=0[/tex]

Now, we can get our solutions.

The first binomial will produce two complex (Not real) solutions.

[tex]x+2=0\\\\x=-2[/tex]

[tex]x-2=0\\\\x=2[/tex]

So our solutions to this equation are

[tex]x=-2\\x=2[/tex]

ACCESS MORE